A pilot study of nalbuphine versus tramadol administered bycontinuous intravenous infusion for postoperative pain control inchildren - Moyao-García, D.; Hernández-Palacios, J. C.; Ramìrez-Mora, J. C.; Nova-Ocampo, A. A. (Acta Biomedica Atenei Parmensis, 2009)
Nalbuphine and tramadol are potent analgesic drugs. Our aim was to preliminarily assess and compare the efficacy and safety of nalbuphine and tramadol for postoperative analgesia in children. In a double-blind design, 24 ASA 1-3 children aged 1 to 10 years undergoing a scheduled surgical procedure were randomly allocated to receive either an intravenous bolus dose of nalbuphine 100 μg/kg immediately before the end of surgery followed by an infusion of 0.2 μg/kg/min for 72 hrs., or an intravenous bolus dose of tramadol 1,000 μg/kg followed by an infusion of 2.0 μg/kg/min for 72 hrs. Postoperative pain control and drug-related adverse events were recorded. Three children who received nalbuphine required an extra bolus dose within the 12 hrs. of post-surgery versus one child in the tramadol group. A similar number of patients in both groups required an increment in the infusion rate within the 72 post-surgery hours. Sedation was observed in 2 children in the nalbuphine group and in 1 child in the tramadol group. Four children presented vomiting with tramadol and two with nalbuphine. Cardiovascular parameters remained within the normal ranges in both groups. In conclusion, the bolus/infusion regimen of tramadol evaluated in this study appears to have better postoperative analgesic efficacy than the bolus/infusion regimen of nalbuphine. These preliminary results require further confirmation by studies with a sample size enough to clearly identify differences in their efficacy as well as in the rate of adverse events secondary to the administration of each of them.